Desmoplakin controls microvilli length but not cell adhesion or keratin organization in the intestinal epithelium - Sumigray, Kaelyn D. (The American Society for Cell Biology, 2012)
Maintaining proper cell–cell adhesion in the intestine is essential for tissue homeostasis and barrier function. This adhesion is thought to be mediated by cell adhesion structures, including tight junctions, adherens junctions, and desmosomes, which concentrate in the apical junctional region. While clear roles for adherens and tight junctions have been established in simple epithelia, the function of desmosomes has not been addressed. In stratified epithelia, desmosomes impart mechanical strength to tissues by organizing and anchoring the keratin filament network. In this paper, we report that the desmosomal protein desmoplakin (DP) is not essential for cell adhesion in the intestinal epithelium. Surprisingly, when DP is lacking, keratin filament localization is also unperturbed, although keratin filaments no longer anchor at desmosomes. Unexpectedly, DP is important for proper microvillus structure. Our study highlights the tissue-specific functions of desmosomes and reveals that the canonical functions for these structures are not conserved in simple epithelium.